Mechanochemical Synthesis and Rapid Consolidation of Nanostructured Nb-ZrO2 Composite - Kim, Seong-Eun; Yoon, Jin-Kook; Shon, In-Jin (AMER SCIENTIFIC PUBLISHERS, 2020)
Nb2O5 and Zr powders at a molar ratio of 1:2.5 were milled using a high-energy ball mill. The mixture powders produced Nb and ZrO2 nanopowders through a solid replacement reaction (Nb2O5 + 2.5Zr -> 2Nb + 2.5ZrO(2)). The synthesized nanopowders were consolidated via high-frequency induction heated sintering (HFIHS) within two min. The mechanical properties (hardness and fracture toughness) of nanostructured 2Nb2.5ZrO(2) composite were then evaluated. Both the hardness and fracture toughness of the 2Nb2.5ZrO(2) composite were higher than those of monolithic ZrO2.
Keywords: MECHANICAL-PROPERTIES; ZRO2